Oscillation of Bounded Solutions of Delay Differential Equations - Jozef Dzurina (Mathematics)
The purpose of this paper is to give new oscillation criteria for second-order delay differential equations <semantics>y″(t)=p(t)y(τ(t)).</semantics> We introduce a new technique for the elimination of bounded nonoscillatory solutions.